Aquafaba Hydrolysates as Functional Ingredients in Muffin Cakes: Effects on Physicochemical Properties, Quality Attributes, and Antioxidant Activity - Bekiroglu, Hatice (Mdpi, 2025)
Aquafaba, a legume cooking water typically discarded as waste, represents a sustainable and plant-based protein source with promising functional applications. In this study, aquafaba hydrolysates were produced by enzymatic treatment with flavourzyme and savinase, yielding two products with distinct degrees of hydrolysis (DH: similar to 10% and similar to 29%). Aquafaba hydrolysates obtained using flavourzyme (AFHs) and savinase (ASHs), together with aquafaba isolate (AI), were incorporated into muffin cakes as partial flour substitutes (5%). The addition of hydrolysates significantly influenced cake quality parameters, particularly antioxidant capacity and textural attributes. Enzymatic hydrolysis, particularly with savinase, produced the most pronounced functional improvements. Technologically, ASHs supplementation significantly enhanced cake expansion, with specific volume values (2.23 mL/g) nearly doubling compared to the control (1.04 mL/g). Crust color was markedly altered, with L* decreasing and a* and b* rising, reflecting darker, more browned surfaces due to intensified Maillard reactions. Both ABTS and DPPH assays demonstrated increased radical scavenging activity with higher DH, while SDS-PAGE confirmed the release of smaller peptide fractions. The ABTS radical scavenging activity of the control muffin (CM, 262.53 mg TE/100 g) significantly increased in AIM (muffin cake substituted with aquafaba protein isolate, 481.87 mg TE/100 g) and reached its highest values in muffins containing AFHs (489.74 mg TE/100 g) and ASHs (530.56 mg TE/100 g), respectively. Hardness, a critical quality parameter particularly relevant to storage stability, decreased in hydrolysate-enriched samples compared with both control and isolate formulations. Oxitest results showed that extended induction periods for hydrolysate-containing cakes (18:47 h) were longer relative to control muffins (15:08 h). Thermal analysis also indicated improved thermal stability in the presence of aquafaba. Overall, the findings demonstrate that aquafaba hydrolysates can be effectively utilized in bakery systems to enhance antioxidant activity, oxidative stability, and technological properties, while simultaneously contributing to sustainable food valorization.
Keywords: aquafaba; enzymatic hydrolysis; SDS-PAGE; texture properties; oxidative stability